Integration of university and school in initial education in Pedagogy (Research, Society and Development, 2020)
Pedagogy academics from Universidade were invited to visit a school community and expose their impressions about the works presented by the school students on the theme ´History, Art, Design and Mathematics of the Mother Churches of the Fourth Colony of Italian Immigration of Rio Grande do South. Thus, a proposal was constructed to establish the integration between the university and the school in which both institutions guided their interdisciplinary studies with the same theme. This study aims to analyze the knowledge manifested in the report of an academic in Pedagogy, based on an interdisciplinary proposal that included a technical visit guided in a school community. For the accomplishment of the interdisciplinary proposal, as well as the university-school integration, the Pedagogy course provided for the Students Awareness Stage, after the Knowledge Mobilization Stage, which included the visit to the school community and, at the end, the Systematization Stage of Knowledge which included structuring and socializing a report. The research has a qualitative and documentary approach. It was verified, in the analyzed document that the academic structured her report talking about the three pedagogical stages guided by the course. It is estimated that this approach is associated with the greater didactic-pedagogical involvement of academics with the interdisciplinary proposal and the use of different didactic resources for further studies, such as the audiovisual resource and a guided technical study trip.